Family-Based Pregnancy Risk Detection With Family-Centered Maternity Care - Aisyah, Risqi Dewi; Suparni, Suparni; Kartikasari, Dian; Abbas, Hasriwiani Habo (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
The ability of pregnant women to detect early high-risk pregnancies is still below average which is one of the causes of complications that can endanger the well-being of the mother and fetus. Family involvement and other social sources of support in the perinatal period are associated with the detection and reduction of pregnancy risk factors. Approach to families in early dedetermination of pregnancy risk can be done with Family Center Maternity Care (FCMC). FCMC is care designed to meet the informational, social, emotional, comfort, and support needs of normal pregnant women during pregnancy and childbirth. The purpose of this study was to determine the determinants of early detection factors for pregnant women with family-based risk with FCMC. This type of research is quantitative and non-experimental with an analytical observational design through a cross-sectional approach. The population in this study was all pregnant women who experienced risk factors in the Kedungwuni I, Kedungwuni II, Bojong Health Center Area as many as 103 pregnant women. The sampling technique used is the Total Population. The results of this study show that there is a positive and statistically significant relationship of knowledge with the implementation of early detection. Pregnant women who have good knowledge have a likelihood of carrying out early detection of pregnancy risk well by 3,193 times higher than respondents with less knowledge (OR=3,193; CI 95%=1.123-9.078; p=0.029). It is hoped that health workers, especially midwives, can involve their families, especially for early detection of the risk of pregnant women so that pregnant women get optimal health services.